The Effect Of Classical Music Therapy On The Level Of Depression Among Schizophrenia Patients In Soeprapto Mental Hospital, Bengkulu Province - Surya Direja, Ade Herman; Juksen, Loren; Sunarsih, Sunarsih (Journal of Applied Nursing and Health, 2021)
Background: Patients with mental disorders experience disturbances in mental function, which include emotions, thoughts, behavior, motivation, self-perception, and perception, which causes a decrease in all mental functions, especially interests, and motivations so that it interferes with a person in the process of living in society. One o the most common mental disorders is schizophrenia. This study aims to study the effect of classical music therapy on depression level in schizophrenic patients at the Soeprapto Mental Hospital, Bengkulu Province Methods: The design in this study used a pre-experimental design. The design form of a pre-experimental study is "pre-test and post-test One Group Design". The population in this study were Schizophrenic patients who experienced depression. The sample used in this study was taken using a purposive sampling technique. This technique is a sampling technique with certain considerations, obtained as many as 25 patients. Data collection in this study used univariate and bivariate analysis using the normality test using the Shapiro Wilk test. Results: The results obtained before providing classical music therapy treatment from 25 Schizophrenic patients had a very severe level of depression with a percentage of (100%) and the results after classical music therapy treatment showed that the level of schizophrenia patients who experienced depression after classical music therapy treatment was 7 patients. The result shows that have a moderate level of depression with a percentage of 28% and 18 patients have a level of severe depression with a percentage of 72%. Based on the results of the Paired sample t-test statistical test there is a significant relationship, the value of t = 20,953 with p = 0.000 <0.05 means significant, so Ho is rejected and Ha is accepted, it can be concluded that there is an effect of using classical music therapy on the level of depression in schizophrenic patients. at RSKJ Soeprapto Bengkulu Province. Conclusion: Based on the result of research there is an effect of using classical music therapy on the level of depression in schizophrenic patients. at RSKJ Soeprapto Bengkulu Province